Managing the real and fiscal effects of banking crises - Klingebiel, Daniela; Laeven, Luc.; World Bank. (Washington, D.C. : World Bank, 2002)
This volume provides two recent analysis, spurred by the recent East Asian crisis, of government responses to financial distress
Includes bibliographical references (p. 49).
osc 9/09/2021
Loans
Keywords: Banks and banking; Financial crises; Banks and banking